PERANCANGAN PERPUSTAKAAN BERBASIS EDU-SOCIAL SPACE DI KEC. PAGEDANGAN, KAB. TANGERANG - Anggrainy, Angelina Anggun Lupita (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2024)
Indonesia still has a low level of reader interest. Specifically, Banten Province's Tangerang District is one of the areas with a low reading interest rate. It's because there's no library in the district of Pagedangan. The library is designed to be a Mixed Use building based on edu-social space with the addition of Co-Working and Food Retail. This is carried out in addition to supporting the library to raise public interest in reading and to support the community's working area in the Pagedangan district. In order to accommodate all of the activities in the building, the library employs the Modern Functionalist concept, which emphasizes the exhibition material, minimizes ornamentation, and form follow function.